Decarboxylation activity of enterococci isolated from rabbit meat and staphylococci isolated from trout intestines - Pleva, Pavel; Buňková, Leona; Lauková, Andrea; Lorencová, Eva; Kubáň, Vlastimil; Buňka, František (Veterinary microbiology, 2012)
The aim of the study was to explore production of seven biogenic amines (phenylethylamine, histamine, cadaverine, tyramine, putrescine, spermine and/or spermidine) by selected staphylococci and enterococci. Thirty three enterococcal strains isolated from rabbit meat (Oryctolagus cuniculus f. domesticus) and 21 staphylococcal strains isolated from intestinal content of trout (Salmo trutta morpha fario) were tested. Production of biogenic amines was evaluated after cultivation of the tested microorganisms in the de Man, Rogosa and Sharpe Broth (enterococci) or in the Brain Heart Infusion Broth (staphylococci). Both the above cultivation media were enriched with selected amino acids (histidine, tyrosine, arginine, ornithine and lysine; 2g/L each) serving as precursors of biogenic amines. After cultivation, levels of the monitored biogenic amines in broths were analysed by a high performance liquid chromatography equipped with a UV/VIS DAD detector. Among 21 staphylococci, 18 strains produced tyramine or cadaverine, 13 strains formed putrescine or phenylethylamine and only one strain generated histamine. Two staphylococcal strains produced cadaverine levels above 1000 mg/L. Among 33 enterococcal strains, 27 formed cadaverine, 18 strains produced tyramine, 10 strains generated phenylethylamine, and 2 strains gave putrescine. Most of the tyramine producing enterococci generated more than 1000 mg/L of this biogenic amine. Production of spermine or spermidine by the studied strains was not proved.
Keywords: Intestines; králíci; Staphylococcus; Rabbits; Decarboxylation; Animals; dekarboxylace; Biogenic Amines; pstruh; biogenní aminy; zvířata; střeva; Meat; Trout; maso; Enterococcus